ANALISIS PENGELOLAAN OBAT DI PUSKESMAS WAARA KABUPATEN MUNA SULAWESI TENGGARA - Khofifah, Dien Noor (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Drug management is a series in health development which involves several aspects, namely needs planning, demand, acceptance, storage, distribution, control, recording and reporting, as well as monitoring and evaluation. The purpose of this study was to determine drug management at the Waara Health Center, Muna Regency, Southeast Sulawesi and its compliance with regulations in force in Indonesia. This research is descriptive in nature, collecting data through observation, document review and interviews with the person in charge of the pharmacy. The results of the study showed that: drug management was in accordance with pharmaceutical service standards at the puskesmas with a percentage value of 100% conformity based on applicable regulations, while in the planning aspect the need to obtain a percentage result of 88.8%, on the storage aspect of the percentage results obtained, namely 91.66% and on the recording and reporting of the percentage results obtained, namely 93.33%. This indicates that drug management at the Waara health center still does not meet drug management standards in accordance with the Regulation of the Minister of Health no.74 of 2016 and the Ministry of Health of 2019.